Regulation of Cryptocurrencies and Blockchain Technologies National and International Perspectives - Girasa, Rosario (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This second edition further explores the regulatory landscape of cryptocurrency, highlighting the rise of Bitcoin, which is based on blockchain technology, and some of the many types of coins and tokens that emerged thereafter. Although Bitcoin and other cryptocurrencies have made national and international news with their dramatic rise and decline in value, nevertheless the underlying technology is being adopted by both industry and governments, which have noted the benefits of speed, cost efficiency, and protection from hacking. Based on numerous downloaded articles, laws, cases, and other materials, the book discusses the digital transformation, the types of cryptocurrencies, key actors, and the benefits and risks. It also addresses legal issues of digital technology and the evolving U.S. federal regulation. The varying treatment by individual U.S. states is reviewed together with attempts by organizations to arrive at a uniform regulatory regime. Both civil and criminal prosecutions are highlighted with an examination of the major cases that have arisen. This second edition specifically explores the creation of stablecoins, governments issuance of their own versions of digital currencies, new regulations that have been enacted and promulgated, and a clearer examination of futuristic evolutions that potentially will have a major impact upon the current cited technologies. Rosario Girasa is Distinguished Professor of Law at the Lubin School of Business, Pace University, USA. He is the author of seven previously published works that range from cyberlaw, law of finance, and shadow banking. He is also the author of approximately 130 articles published in diverse U.S. and international journals.
Chapter 1. The Digital Transformation -- Chapter 2. Technology Underlying Cryptocurrencies and Types of Cryptocurrencies -- Chapter 3. Legal Issues of Digital Technology -- Chapter 4. US Federal Regulation of Virtual Currencies -- Chapter 5. States' Regulation of Virtual Currencies -- Chapter 6. Criminal and Civil Enforcement of Virtual Currencies -- Chapter 7. Central Bank Digital Currencies -- Chapter 8. International Regulation -- Chapter 9. Conclusion: The Future of Cryptocurrencies.
Keywords: Financial engineering; Financial services industry; Finance -- Law and legislation; Financial Technology and Innovation; Financial Services; Financial Law